Remoção de ferro e manganês de águas subterrâneas por resinas de troca iônica comerciais - Piaia, Andreia Aparecida (2021)
Underground water resources have become an alternative for water supply for consumption, however, the problem is mainly associated with the presence of iron (Fe) and Manganese (Mn) in wells with exploration potential, thus requiring more attention to technologies directions in removing these metals from the water. Among the treatment technologies, the adsorption process has great prominence in the removal of metallic contaminants even in low concentrations. The objective of this work is the use of commercially available adsorbent materials such as activated carbon and ion exchange resins for the treatment of groundwater contaminated with Iron and Manganese in order to meet the maximum specification regulations of 0.1 mg/L for Mn and of 0.3 mg/L for Fe. The resins used in this research were Dowex Marathon C; SSTC60; Lewatit TP 207 and activated charcoal from bones. The methodology used was to carry out batch adsorption experiments, obtaining equilibrium data for the construction of isotherms, carrying out tests in a continuous system to elaborate the adsorption kinetics for each metal and adsorbent material, evaluating the regenerating potential of each resin, in addition to verifying the adsorption of Na, K, Ca and Mg metals present in the sample during the treatment. After obtaining the data, it was possible to design a system with columns connected in series for the continuous treatment of groundwater. After analyzing the results, it was found that the adsorbent Dowex MarathonTM C obtained the best performance in the adsorption of Fe2+ in groundwater, producing water that meets potability standards and can be regenerated with both HCl and NaCl. The Mn2+ ion can be removed with Dowex MarathonTM C and SSTC60 resins with results superior to Iron at the same concentration, the resins were efficiently regenerated with the NaCl solution. It was also verified that the cations Na, K, Ca and Mg were also removed from the water and there were no significant changes in relation to the pH of the water, which remained within the value allowed by legislation.